2013
DOI: 10.1186/ar4140
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol promotes the development of a fibrotic phenotype and is increased in the serum of patients with systemic sclerosis

Abstract: IntroductionSystemic sclerosis (SSc) is more prevalent in women. Our goal is to determine the effects of 17β-estradiol (E2) on the development of fibrosis and to compare circulating levels of estrogens in SSc patients and healthy controls.MethodsUsing primary human dermal fibroblasts, we evaluated the effect of E2 on fibronectin (FN) expression with and without the estrogen receptor (ER) antagonist ICI 182,780, inhibitors of signaling, propyl-pyrazole-triol, an ERα specific ligand, and genistein, an ERβ select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(83 citation statements)
references
References 46 publications
2
75
2
4
Order By: Relevance
“…However, ERβ overexpression decreases JNK phosphorylation and protects intact male and female mouse hearts against fibrosis [ 16 ]. Furthermore, a recent study highlighted the fact that ERα activation in fibroblasts increased fibronectin production [ 31 ]. On the other hand, in male mice, ERβ has been demonstrated to have a beneficial role on cardiac fibrosis, at least in part by inhibiting TGF-β1 and collagen I expression in intact male and female mice (13) and OVX female mice [ 10 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, ERβ overexpression decreases JNK phosphorylation and protects intact male and female mouse hearts against fibrosis [ 16 ]. Furthermore, a recent study highlighted the fact that ERα activation in fibroblasts increased fibronectin production [ 31 ]. On the other hand, in male mice, ERβ has been demonstrated to have a beneficial role on cardiac fibrosis, at least in part by inhibiting TGF-β1 and collagen I expression in intact male and female mice (13) and OVX female mice [ 10 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this set of patients, we previously demonstrated that treatment with finasteride results in basal cell hyperplasia [11] , which is one hallmark of increased local estrogen levels [37] . Interestingly, higher estrogen levels can also result in increased collagen deposition [38] , suggesting that estrogen-stimulated deposition of collagen by fibroblasts, myofibroblasts, and fibrocytes through 5α-RI treatment may be contributing to remaining LUTS. However, in this study, we found no association between treatment with finasteride and changes in collagen levels.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, using primary human dermal fibroblasts, the effect of 17b-estradiol on expression of fibronectin has been evaluated with and without ICI 182, 780 (Faslodex), a steroidal estrogen antagonist (this is the first in a new class of agentan estrogen receptor downregulator) [38].…”
Section: • Rheumatoid Arthritismentioning
confidence: 99%